1996
DOI: 10.1021/jm960231+
|View full text |Cite
|
Sign up to set email alerts
|

H and 13C NMR Relaxation Studies of Molecular Dynamics of the Thyroid Hormones Thyroxine, 3,5,3‘-Triiodothyronine, and 3,5-Diiodothyronine

Abstract: 1H and 13C NMR spin-lattice relaxation times and 13C{1H} nuclear Overhauser enhancement factors have been measured for the thyroid hormones thyroxine, 3,5,3'-triiodothyronine, and 3,5-diiodothyronine, with the aim of determining the internal molecular dynamics in these molecules. Spin-lattice relaxation times of protons on the two aromatic rings of these hormones show remarkable differences, with values for the hydroxyl-bearing ring being a factor of 4-12 times larger than those for the alanyl-bearing ring. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…In addition, many of these affected bands show irregular contours that appear as better defined shoulders upon spectral subtraction of the DLPC spectrum. NMR experiments of T3 in methanol solution have shown the presence of two conformers of the hormone, coexisting in equilibrium . They are called T3p and T3d when the iodine atom in the ring‐β is in proximal or distal orientation to the ring‐α, respectively (see Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, many of these affected bands show irregular contours that appear as better defined shoulders upon spectral subtraction of the DLPC spectrum. NMR experiments of T3 in methanol solution have shown the presence of two conformers of the hormone, coexisting in equilibrium . They are called T3p and T3d when the iodine atom in the ring‐β is in proximal or distal orientation to the ring‐α, respectively (see Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The band corresponding to the antisymmetric ν(C α –I) (187 cm −1 in T3) is not shifted but shows a shoulder at ~175 cm −1 in T3/DLPC. The shoulders of the main symmetric and antisymmetric ν(C α –I) bands are interpreted as evidence of the presence of two conformers of T3, in agreement with published reports . The Raman spectrum of pure T4 shows two very strong bands at 221 and 192 cm −1 which are associated to the symmetric ν(C β –I) and ν(C α –I) modes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The conformational flexibility and internal dynamics in thyroid hormones in solution have been studied earlier by NMR spectroscopy. Similar to the three-dimensional structures of thyroid hormones observed in the X-ray structures, these studies also indicated the roughly perpendicular arrangement of the two iodinated rings and the rapid movement of the phenolic ring about the diphenyl ether linkage. As discussed earlier, rotation of the phenolic ring about the O3–C1′ bond in T3 gives rise to the formation of proximal and distal conformers.…”
Section: Resultsmentioning
confidence: 52%
“…A simple calculation based on ring current effects suggests that the maximum possible chemical shift difference of the H2 and H6 protons in such a twist−skewed conformation is 0.4 ppm, and this is achieved when φ‘ = ±30°. However, this is not likely to be the factor responsible for the coalescence process observed in solution because interchange between symmetry-related skewed forms in solution is extremely rapid (as demonstrated by 13 C T 1 measurements) and will result in an averaged resonance for H2 and H6 at all accessible temperatures.…”
Section: Discussionmentioning
confidence: 99%